2018
DOI: 10.2174/1874434601812010248
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection Among Women Aged (18-40) Years Old in Kirkuk City, Iraq

Abstract: This is a cross-sectional descriptive study which was carried out in the outpatient clinics for Obstetrics and Gynecology and Urology at Kirkuk General Hospital over the period of 6 months from 1st of February-1st of September,2017. The sample of the study included 450 women who were randomly selected from the following three groups: pregnant women n=150, married women n=150, and unmarried women n=150. Each woman was interviewed using a Questionnaire containing personal information such as age, occupation, Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
5
17
2
1
Order By: Relevance
“…These results suggests that besides literacy and economic status awareness regarding UTI is more necessary, so awareness programme should be conducted to make people aware about cleanliness and personal hygiene. Similar study on the basis of patient's literacy level and residential status was done by Almukhtar et al, in Iraq and they found that majority of women [7] patients were illiterate and from rural areas. Another study carried out on pregnant women residing in both rural and urban area of Tanzania shows that prevalence of UTI was higher in rural area and their [17] percentage was (12.5%).…”
Section: Relation Of Uti With Literacy Socio-economic Status and Ressupporting
confidence: 69%
See 1 more Smart Citation
“…These results suggests that besides literacy and economic status awareness regarding UTI is more necessary, so awareness programme should be conducted to make people aware about cleanliness and personal hygiene. Similar study on the basis of patient's literacy level and residential status was done by Almukhtar et al, in Iraq and they found that majority of women [7] patients were illiterate and from rural areas. Another study carried out on pregnant women residing in both rural and urban area of Tanzania shows that prevalence of UTI was higher in rural area and their [17] percentage was (12.5%).…”
Section: Relation Of Uti With Literacy Socio-economic Status and Ressupporting
confidence: 69%
“…Some gram positive bacteria like S. aureus and E. faecalis. The predisposing factors responsible UTI include [7] sexual contact, urinary catheter and diabetes. It has been estimated that women are more susceptible to UTIs due to poor hygiene, sexual intercourse, use of contraceptives and easy excess of bladder while males are susceptible to UTIs due to kidney stone and prostrate problems.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized as the second most frequent infection in the general population and occurs in all ages, but there is a higher frequency in three age groups: children up to 6 years of age, young women with active sex life and elderly adults over 60 years of age. 9,10 Most infections caused by Enterobacteria that produce the enzyme KPC, occur in patients with impaired immunity, who have comorbidities. These are transplant patients, neutropenic, using invasive ventilatory support, those in ICU, with long periods of hospitalization, who present a high risk of infection or colonization for microorganisms with a broad spectrum of resistance, and also with invasive devices such as: catheter, probe, peripheral venous puncture, LPP, tracheostomy, among others.…”
Section: Resultsmentioning
confidence: 99%
“…15 To reduce these high rates and mortality, it is necessary that the hospital adopt preventive measures, such as: establish contact precautions in patients with suspicion, confirmation of infection or colonization by multidrugresistant microorganisms, make the correct use of PPE and follow the recommendations of the precautions, make swab culture in conscious patients and put contact precautions until the result of the examinations, make the use of materials and equipment exclusive (sphygmomanometer, thermometer, stethoscope). 2,4,[8][9][10] Talk about cleaning care using soap and water and disinfection with alcohol 70% of the surfaces and materials that come into contact with the patient, as recommended by the CCIH. Emphasize the rational use of antimicrobial by physicians.…”
Section: Resultsmentioning
confidence: 99%
“…Urinary tract infections (UTIs) are characterized by colonization, invasion and multiplication of microorganisms in the urinary system (1) (2) . UTI is an infection of the urinary system that may involve the lower urinary tract or both the lower and upper urinary tract (3) .…”
Section: Introductionmentioning
confidence: 99%